FROM THE EDITOR. - Yerxa, Donald A. (Fides et historia, 2012)
An introduction is presented that discusses issue articles on topics including the impact of historians' religious faith on their work as historians, historian Herbert Butterfield's book "The Whig Interpretation of History," and religious aspects of the Second Boer War.